The Proof-of-the Concept of Biochar Floating Cover Influence on Swine Manure pH: Implications for Mitigation of Gaseous Emissions From Area Sources - Meiirkhanuly, Zhanibek; Koziel, Jacek A.; Bialowiec, Andrzej; Banik, Chumki; Brown, Robert C. (Frontiers in Chemistry, 2020)
Mitigation of potentially hazardous and malodor compounds emitted from animal waste is needed to improve the sustainability of livestock agriculture. Swine manure emits ammonia, hydrogen sulfide, greenhouse gases, and odorous volatile organic compounds. Bacteria control the generation of these compounds and also depend on the pH of manure. Influencing swine manure pH, especially on the liquid-air interface, may lead to a reduction of emission of these compounds. The objective of this experiment was to test highly alkaline and porous (HAP) modified biochar with pH=9.2 and red oak (RO) biochar with pH=7.5 influence on swine manure pH acquired from the outdoor storage and deep pit storage under a barn. HAP and RO biochars were topically applied on the outdoor-stored (pH=7.55), and pit (pH=8.00) manures and spatial pH (every 1 mm of depth) were measured on days 0, 2, and 4. Results showed that HAP biochar increased outdoor-stored manure pH, particularly within the top 10 mm of depth, where pH ranged from 9.00 to 7.66 on day 4. Both biochars decreased pit-stored manure pH in comparison with control on day 4. However, differences were not considerable. The reason for the insignificant effect of biochars on pit manure was likely due to its higher buffer capacity in comparison with the outdoor-stored manure.